Design and Evaluation of C-Band Microstrip Antenna Array for Portable Ground Surveillance Radar - Matheus Edward, Ian Josef; Hariyadi, Tommi; Shalannanda, Wervyan; Bharata, Endon; Danudirdjo, Donny; Hidayat, Yosi A.; Hariyanto, Dharma Favitri; Mustafa, Alvin; Kusmadi; Nugroho, Sapto Adi; Ridwan, Nerissa Arviana (Ital Publication, 2025)
This study aims to design, simulate, fabricate, and evaluate a high-gain C-band microstrip antenna array with a corrugation plate for Portable Ground Surveillance Radar (PGSR) applications, addressing the need for compact, high-performance antennas in border security operations. The proposed design targets a minimum gain of 20 dBi, a horizontal beamwidth of ≤ 2.8°, a vertical beamwidth of ≤7.5°, horizontal polarization, and compact physical dimensions for field portability. The methodology involved electromagnetic simulations to optimize the slit-patch array geometry, fabrication using Rogers RO-4350B substrate for its stable dielectric properties, and performance validation in an anechoic chamber using a vector network analyzer. The fabricated prototype achieved strong agreement with simulations in key metrics: realized gain exceeded 20 dBi, return loss reached -27.35 dB, and SWR was approximately 1.2, confirming effective impedance matching. The corrugation plate enhanced impedance matching, improved transmission efficiency (S21), and reduced reverse isolation (S12), while S22 remained stable. Despite these strengths, the measurement beamwidths, especially vertical beamwidth ( 30°), exceeded both simulation and target values, highlighting fabrication precision and alignment as areas for improvement. The novelty of this work lies in integrating a corrugation plate to improve impedance matching and the correlation between simulation and measurement, offering a practical, tuneable enhancement to microstrip antenna arrays for PGSR and similar radar systems.